1998
DOI: 10.1128/iai.66.12.5805-5811.1998
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hydroxy Fatty Acids and Prostaglandin E2in Gingival Tissue

Abstract: Bacterial hydroxy fatty acids and alpha-hydroxy fatty acids have been demonstrated in complex lipid extracts of subgingival plaque and gingival tissue. However, little is known about the relationship between these hydroxy fatty acids in plaque and gingival tissues or the significance of these complex lipids in promoting inflammatory periodontal disease. The present study determined the percentages of ester-linked and amide-linked hydroxy fatty acids in complex lipids recovered from plaque and gingival tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A) Characteristic mass spectra for the two major phosphoethanolamine dihydroceramides of P. gingivalis . See (9) for the interpretation of the mass spectra and Fig. 2 for a description of other products that can produce the same mass spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A) Characteristic mass spectra for the two major phosphoethanolamine dihydroceramides of P. gingivalis . See (9) for the interpretation of the mass spectra and Fig. 2 for a description of other products that can produce the same mass spectra.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report demonstrated elevated levels of 3‐OH iso C 17:0 in gingival tissue lipid extracts from periodontitis sites compared with healthy/mildly inflamed sites (6). A subsequent report indicated that the majority of 3‐OH iso C 17:0 in lipid extracts of gingival tissue is amide‐linked, suggesting contamination of diseased gingival tissues with bacterial ceramide lipids that contain 3‐OH iso C 17:0 (9). As these lipids could be important in the pathogenesis of destructive periodontal diseases, the purpose of this investigation was to determine whether the dihydroceramide lipids of P. gingivalis could be detected in lipid extracts of periodontally diseased teeth and gingival tissues.…”
mentioning
confidence: 99%
“…This model therefore predicts that adult periodontitis is, in part, a lipid-mediated disease. Supporting this notion is the recently reported direct relationship between bacterial lipid penetration into gingival tissue and altered lipid metabolism within gingival tissue leading to elevated recovery of alpha hydroxy fatty acidcontaining complex lipids (6). While the signi®cance of altered lipid metabolism within gingival tissues is not clear, prostaglandin E 2 levels directly correlate with alpha hydroxy fatty acid-containing lipids in gingival tissue samples (6).…”
Section: Discussionmentioning
confidence: 98%
“…Regardless of the disease status of periodontal connective tissue, the predominant cell type recovered in gingival connective tissue is the ®broblast (5). Gingival ®broblasts are expected to be exposed to the previously mentioned bacterial lipids given the impressive recovery of bacterial lipids in diseased periodontal tissues (2,6). Furthermore, gingival ®broblasts are capable of secreting impressive levels of prostaglandin E 2 (7), a soluble host factor capable of proin¯ammatory eects with potentially adverse eects on bone and connective tissue homeostasis.…”
mentioning
confidence: 99%
“…Osteoblasts exposed to MTA produce elevated levels of interleukins-1 and -6 (Koh et al 1998). Both of these interleukins can cause the release of PGE 2 from fibroblasts (Richards & Rutherford 1988, Nichols & Maraj 1998, Lahiri et al 2001. Figure 1 Prostaglandin E 2 production (pg mL )1 ) by macrophages exposed to test materials.…”
Section: Discussionmentioning
confidence: 99%